The role of budget constraints in sequential elimination tournaments - Malin Arve; Olga Chiappinelli (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Motivated by the EU concept of Pre-Commercial Procurement and the massivepresence of SMEs in the European economy, we study how budget constraints affect R&D effort in sequential elimination tournaments. We show that introducingbudget constraints leads to a non-monotonicity in unconstrained contestants' effort.Furthermore, we show that if the budget asymmetry is not too large, unconstrainedcontestants exert higher effort than when faced with unconstrained contestants only.
Keywords: D72; H57; 330; Pre-Commercial Procurement; Contests; Budget constraints